rd Ethical climate and its effect in teaching hospital: A vision from 3 eye - Kumar Bansal, Anupam; Parmar , Pragnesh B; Bansal, Prerna; Patel , Reekee; Barai , Pankaj H; Thomas , Ebbie (Journal of Indian Academy of Forensic Medicine, 2019)
Ethics are the basic things to be followed everywhere and more importantly at work place. In the same way, ethical climate plays a key  role in deciding the working environment of a teaching hospital and medical college. The present study aimed to investigate the  correlation between ethical climate and its effects in teaching hospital on the basis of perception of the nurses employed in a teaching  hospital regarding the ethical climate in their work environment. It was a descriptive, cross-sectional study, which was conducted on  200 nurses working at Parul Sevashram Hospital and Medical College, Vadodara, Gujarat, India. For data analysis, descriptive and  inferential statistics were used. Olson's Hospital Ethical Climate Survey (HECS), a self-administered standard questionnaire, was  used to assess the nurses' perceptions of the hospital ethical climate. Mean ethical climate scores of nurses for colleagues, patients,  managers, hospital and physicians' factors were 4.49±0.491, 4.25±0.489, 4.70±0.353, 4.38±0.402, and 4.53±0.454, respectively. The  total mean score of ethical climate was 4.49±0.288. The comparison among the mentioned factors indicated that managers (P=0.000)  factor acquired the highest score. In addition, organizational ethical climate did not show any significant association with age, sex,  marital status, education status and work experience. The highest score of ethical climate belonged to managers' factor, while the  minimum score was related to patients. Regarding the role of ethical climate in the improvement of nurses' performance, planning for  enhancing the ethical climate seems to be mandatory.
Keywords: Ethical climate; HECS; Teaching Hospital; Nurses